ANALISIS ASPEK RELIGIUSITAS TERHADAP ETIKA BISNIS PEDAGANG PASAR MUSLIM PUSAT PASAR KOTA MEDAN - Akrim Ashal Lubis (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2017)
This study aims to analyze the religiosity aspect of the business ethics of Muslim market traders in the central market of Medan. The method used in this study with the approach of literature review and field studies in the central market of Medan city with a population of 490 respondents with sampling technique of 97 respondents. The aspect of religiosity is limited by one variable of worship practice which includes prayer, fasting, zakat, and hajj. Furthermore, the variables of business ethics include value of honesty, fairness, discipline, and responsibility. The results of this study indicate that religious aspects contribute in improving the business ethics of central traders of Medan city market. Thus, the higher the level of religiosity of market traders, the higher the ethics in business.